Los biocombustibles y la producción de etanol - Barrientos Felipa, Pedro (2008)
Nowadays, a big problem for the countries has been their dependency to oil, what it has shown the weaknesses of them. Hence, the need to look for alternative fuel that can be relatively cheaper, easy to access, and more environmentally friendly. On this scenario, the biofuels –among them the ethanol– have the possibility to be produced in high volumes that can be even exported, like in our country. However, the production could imply some risks against the foodproduction. In this new and growing market, the role of the Government is important to protect the consumers. Somehow, the food production could be affected.